BRAND AWARENESS LEVEL OF PAWON JENONK AS ONE OF THE MICRO-SCALE FOOD INDUSTRIES IN BANDUNG, INDONESIA - Hanifatur Aziz Nur Ishmah; Sulistyodewi Nur Wiyono; Dini Rochdiani; Nur Syamsiyah (Universitas Tadulako, 2021)
Brand awareness is one of the brand equity components that holds a significant role in brand popularity and brand profitability. However, Pawon Jenonk has been encountering popularity and profitability issues for 3 years. Therefore, this study is executed to measure consumers' brand awareness of Pawon Jenonk and its ability to indicate the brand’s popularity and profitability or the contrary. In this study, the level of brand awareness is measured from both its depth and breadth. This study used a quantitative research design using a survey method to collect the data. The population is 160 consumers who purchased its product between December 2020 – January 2021 and simple random sampling was used to choose 150 consumers of the population. In analyzing the collected data, descriptive statistic analysis was used by categorizing the respondents’ total rating score towards the brand awareness instruments. The result shows that 59,33% of the respondents have a high level of brand awareness, 36,00% of the respondents have a moderate level of brand awareness, and 4,67% of the respondents have a low level of brand awareness. From that result, it can be stated that Pawon Jenonk has been quite successful in establishing its consumers' ability to recognize and recall the brand but not so much in establishing the consumers’ consideration to purchase and consume its products. It can be stated that this study indicates a linkage between brand awareness with the brand’s popularity and profitability. The result also proved that Pawon Jenonk’s issues are related to its brand awareness. Therefore, it can be concluded that the level of brand awareness can indicate brand popularity and profitability condition or the contrary.